2023
DOI: 10.1039/d3cp04666d
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated lithium-ion diffusion via a ligand ‘hopping’ mechanism in lithium enriched solvate ionic liquids

Timothy Harte,
Bhagya Dharmasiri,
Garima S. Dobhal
et al.

Abstract: Solvate ionic liquids (SILs), equimolar amounts of lithium salts and polyether glymes, are well studied highly customisable “designer solvents”. Herein the physical, thermal and ion mobility properties of SILs with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Finally, attempts have been made to improve the SILs properties by adding an excess of the lithium salt to convert them to HCEs (i.e., [O]/[Li] < 4) . These HCE-SIL electrolytes have been shown to have improved oxidative stability and Li + transport but low ionic conductivity due to their high viscosities. , These studies demonstrate that to enhance the ionic transport of SILs and HCE-SILs while maintaining their advantageous electrochemical properties, it is critical to have a molecular understanding of the influence of ion–solvent and ion–ion interactions on their transport properties.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, attempts have been made to improve the SILs properties by adding an excess of the lithium salt to convert them to HCEs (i.e., [O]/[Li] < 4) . These HCE-SIL electrolytes have been shown to have improved oxidative stability and Li + transport but low ionic conductivity due to their high viscosities. , These studies demonstrate that to enhance the ionic transport of SILs and HCE-SILs while maintaining their advantageous electrochemical properties, it is critical to have a molecular understanding of the influence of ion–solvent and ion–ion interactions on their transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that these Raman modes are not well suited for assigning ionic speciation because of an ambiguity in the spectroscopic signatures for the different ionic species . Other studies have used indirect methods, such as the NMR self-diffusion coefficient ratios and thermal stability of HCEs and SILs, to deduce the possible local structure of Li + . , Molecular dynamics simulations have also been applied to explore the Li + solvation structure and dynamics in HCEs, but most studies do not have the accuracy to reproduce experimental observations . Overall, these previous studies reveal an incomplete picture of the Li + solvation environment in HCEs and SILs, highlighting the need for a better description of the Li + solvation structure and dynamics in relation to the transport properties.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations